2011
DOI: 10.1002/pip.1072
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of photoplating for laser doped solar cells

Abstract: The use of laser doping in solar cell fabrication has received increased attention in recent years, especially due to its ability to form a selective emitter without subjecting the wafer to prolonged high temperature processes and likely corresponding degradation. At the University of New South Wales, a novel laser doping method was developed that combines the formation of the selective emitter with a self-aligned metallisation pattern. This paper investigates the influence of different plating methods on shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…(iv) For laser based processing such as laser doping or ablation, LIP can avoid deposition in regions where microcracks are generated since the photovoltage is low [61]. This is unlike electroless plating in which plating takes place on the exposed Si and hence increases the formation of shunts in laser damaged areas.…”
Section: Light Induced Plating (Lip)mentioning
confidence: 99%
“…(iv) For laser based processing such as laser doping or ablation, LIP can avoid deposition in regions where microcracks are generated since the photovoltage is low [61]. This is unlike electroless plating in which plating takes place on the exposed Si and hence increases the formation of shunts in laser damaged areas.…”
Section: Light Induced Plating (Lip)mentioning
confidence: 99%
“…For dry laser‐doping, the concentration of the phosphorus dopant source and spin‐coating conditions as well as the laser parameters can affect the properties of the laser‐doped regions and consequently also the subsequent LIP . Recent reports have demonstrated that both dry and wet approaches can result in heavily‐doped grooves, which can be metallised using LIP nickel/copper/silver or LIP nickel/silver . Because the patterning process also forms the selective‐emitter, metallisation of laser‐doped front surface grids is a self‐aligning process, thus making the technology attractive for manufacturing.…”
Section: Front‐grid Metallisationmentioning
confidence: 99%
“…For dry laser-doping, the concentration of the phosphorus dopant source and spin-coating Silicon solar cell metallisation A. Lennon, Y. Yao and S. Wenham conditions as well as the laser parameters can affect the properties of the laser-doped regions and consequently also the subsequent LIP [64]. Recent reports have demonstrated that both dry and wet approaches can result in heavilydoped grooves, which can be metallised using LIP nickel/ copper/silver or LIP nickel/silver [27,56,57,59,61,62,65].…”
Section: Laser Dopingmentioning
confidence: 99%
“…The carrier concentration of the heavily B-doped surface layer is larger than approximately 10 19 cm À 3 . A laser doping method has been developed for heavily doped surface layers [2][3][4][5][6][7][8]. This technique has some advantages associated with the use of laser light.…”
Section: Introductionmentioning
confidence: 99%